2009
DOI: 10.1002/pbc.22108
|View full text |Cite
|
Sign up to set email alerts
|

Oral health and dental anomalies in patients treated for leukemia in childhood and adolescence

Abstract: The treatment of ALL causes a significant increase in the number of dental anomalies. Their GBI and VPI were also elevated. Changes in salivary glands during treatment did not affect saliva flow permanently. Follow-up of these patients by an oral health team is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
2
12

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 25 publications
6
69
2
12
Order By: Relevance
“…[38] Since a reduced SFR has been reported in children with ALL and that a diminished SFR favors accumulation of dental plaque on tooth surfaces, it may be hypothesized that children with ALL may be more susceptible to dental caries as compared to medically healthy children. [37] In this study, no significant difference is observed in DMFT of both groups, which supports the results of Maciel et al [39] / Kinirons et al [40] studies; it can be due to sanitarian educations and parents' awareness.…”
Section: Discussionsupporting
confidence: 81%
“…[38] Since a reduced SFR has been reported in children with ALL and that a diminished SFR favors accumulation of dental plaque on tooth surfaces, it may be hypothesized that children with ALL may be more susceptible to dental caries as compared to medically healthy children. [37] In this study, no significant difference is observed in DMFT of both groups, which supports the results of Maciel et al [39] / Kinirons et al [40] studies; it can be due to sanitarian educations and parents' awareness.…”
Section: Discussionsupporting
confidence: 81%
“…Sugere-se que em pacientes oncológicos pediátricos haja um plano de prevenção e controle da cárie dentária, tendo em vista que esses indivíduos podem apresentar lesões de cárie dentária com maior frequência, pois estão sujeitos à Concordando com esses resultados, no estudo de Maciel et al 17 realizado com crianças em tratamento oncológico, o índice de sangramento gengival e o índice de placa visível foram elevados em comparação com o grupo controle sem câncer. As condições de saúde em que os portadores de câncer se encontram, como a baixa no número de plaquetas, podem ocasionar sangramentos gengivais.…”
Section: Discussionunclassified
“…Isso logo é seguido pela perda dessa camada e substituição pela mucosa atrófica, a qual é edemaciada, eritematosa e friável. Subsequentemente, aparecem áreas de ulceração com a formação de uma membrana superficial fibrinopurulenta amarelada e removível 3 . A dor, a ardência e o desconforto são sintomas que podem se acentuar durante a alimentação ou a higiene bucal 8 .…”
Section: Revisão De Literaturaunclassified
“…Entre os efeitos tardios do tratamento oncológi-co, observa-se que as alterações odontológicas e do desenvolvimento facial são sequelas do tratamento oncológico e tem maior impacto, pois as crianças vivem por um período maior de tempo, necessi- tando, portanto, de cuidados preventivos 3 . Quanto mais jovem for o paciente, maior é a possibilidade das terapias oncológicas afetarem a saúde bucal e o desenvolvimento dentário e facial.…”
Section: Introductionunclassified